DEVELOPMENT OF THREE DIFFERENTIATED MATHEMATICS LEARNING MODULES: A BLENDED AND SCAFFOLD-BASED LEARNING MATERIALS FOR NEW NORMAL REMOTE LEARNING - Santillan, Jesus Parena (Journal of Agriculture and Technology Management, 2023)
Effective strategies in the new normal education system are the main concern of the Department of Education amidst pandemic. Teacher-experts are encouraged to innovate intervention-learning materials as a support mechanism to address the issues on distance and remote teaching and learning process and provide the quality of education in the Philippines under the (K to 12) Curriculum. This study developed learning modules considering the students' differences and preferred learning styles applicable in this current situation. The study utilized descriptive-exploratory with developmental research design. The code-switch instructions (Tagalog-English) on the supplement video lessons was the key feature of three (3) differentiated learning materials based from the qualitative findings of this study. The contents of these are lessons about Solving Linear Inequalities since the researcher found it to be the least learned area in Mathematics 8. Moreover, the developed learning modules were highly accepted by the selected expert respondents of the study